Regulasi Diri dan Fear of Missing Out (FOMO) pada Mahasiswa Pengguna TikTok - Cahyati, Ma'rifatullillah Destiana; Suhadianto, Suhadianto; Rista, Karolin (JIWA: Jurnal Psikologi Indonesia, 2025)
Abstract FOMO is the fear of losing social opportunities that is closely related to the use of the internet and social media, one of which is TikTok. Self-regulation is behavior or management of thoughts and behaviors based on oneself. This research aims to examine the relationship between self-regulation and fear of missing out (FoMO) in student users of TikTok. The sample from this research was 175 students who used TikTok aged 18-25 years in Surabaya. This research uses descriptive quantitative methods with correlational techniques. The instruments used consist of the FoMO scale with 16 items, and the self-regulation scale with 25 items which have been tested for validity and reliability. Data analysis was carried out using the Spearman rho correlation test to evaluate the influence of the independent variable (self-regulation) on the dependent variable (fear of missing out) or FoMO. The results of the analysis show that self-regulation has a significant negative relationship with fear of missing out (p < 0.05). In other words, the higher the fear of missing out, the lower the self-regulation, and conversely, the lower the fear of missing out, the higher the level of self-regulation. Keywords: Fear of Missing Out, Self-Regulation, TikTok Abstrak FOMO adalah ketakutan kehilangan kesempatan sosial yang erat kaitannya dengan penggunaan internet dan sosial media, salah satunya TikTok. Regulasi diri adalah perilaku atau pengelolaan pikiran dan perilaku yang didasari oleh diri sendiri. Penelitian ini bertujuan untuk mengkaji hubungan antara regulasi diri dengan fear of missing out (FoMO) pada mahasiswa pengguna TikTok. Sample dari penelitian ini adalah mahasiswa pengguna TikTok di yang berusia 18-25 tahun di Surabaya yaitu 175 orang. Penelitian ini menggunakan metode kuantitatif deskriptif dengan teknik korelasional. Instrumen yang digunakan terdiri dari skala FoMO dengan 16 item, dan skala regulasi diri 25 item yang telah diuji validitas dan reliabilitasnya. Analisis data dilakukan dengan uji korelasi Spearman rho untuk mengevaluasi pengaruh variabel bebas (regulasi diri) terhadap variabel terikat (fear of missing out) atau FoMO. Hasil analisis menunjukkan bahwa regulasi diri memiliki hubungan negatif yang signifikan terhadap fear of missing out (p < 0,05). Dengan kata lain, semakin tinggi fear of missing out maka semakin rendah regulasi diri, dan sebaliknya semakin rendah fear of missing out maka semakin tinggi tingkat regulasi diri. Kata kunci: Fear of Missing Out, Regulasi Diri, TikTok